Real-time applications and novel manufacturing strategies of incremental forming: An industrial perspective. (2021) - Kumar, S. Pratheesh; Elangovan, S.; Mohanraj, R.; Boopathi, S.
Abstract: Incremental Sheet-Metal Forming (ISMF) is a flexible and evolving metal forming technology for rapid free-form prototyping and small-batch metal components manufacturing. The end product has evolved by means of localized deformation in addition bi-axial stretching during that deforming tool squeezed on blank with predefined process variables. Owing to a unique process advantages and low manufacturing cost, its market requirement continuous enlargement and the process gradually transforms from prototyping to real-time manufacturing perspective. Over the preceding decades, ISMF technology has been adequately established in research and development, although it is less explored in the real-time industrial environment. The main intention of this exploration is to bring-forth insight into potential applications such as aviation, automotive, bio-medical, research and concept development through implementation of ISMF. Further, component evaluation performed to establish a convenient and feasible solution from deep-drawing and hydro-forming. For customized part forming, conventional forming process seems to be insufficient. Due to industrial transformation, dependent on cost-effectiveness, even prototyping and low-volume manufactured components relying on superior quality. Although, understanding the effect and influence of process variable, which needs the data analysis with implementing the optimization models and Artificial neural-network (ANN) model. These types of analysis majorly focus on monitoring and predict target values at each cycle and also reconfigure to optimistic or organize the iterative method for describing the appropriate process guidelines. Further, recent advances in ISMF process variants are explored, while looking at the benefits of ISMF for real-time part production. ISMF continues to mature into technology for production applications, while exploring the potential field to transform the way sheet components are fabricated in the new-era of digital manufacturing. This study will, in turn, enhance the capabilities of ISMF technology, which has grown significantly over the preceding decades, allowing technology adopters to innovate new design principle and achieve greater production flexibility.